Reduced drinking in alcohol dependence treatment, what is the evidence? - Mann, Karl; Aubin, Henri-Jean; Witkiewitz, Katie (European addiction research, 2017)
Abstinence from alcohol has been the prevailing treatment goal for individuals with alcohol dependence (AD) within the context of specialty alcohol treatment. Yet, alcohol use has been conceptualized as existing on a continuum. Importantly, most people who meet criteria for AD and could benefit from treatment never receive treatment. About half of these individuals do not seek treatment because they report a desire to continue drinking. To increase acceptability of treatment, reductions in alcohol consumption have been examined as alternative outcomes in treatment trials for AD. The current study reviews data which indicate that long-term reduction in alcohol consumption among patients with AD is possible. Controlled studies have tested reduced alcohol consumption and show sustained improvements in drinking reductions for many patients following behavioral treatments and pharmacotherapy. Evidence-based treatment guidelines and medicines development guidance authorities have taken note of these developments and accept “intermediate harm reduction” (European Medicines Agency) or “low-risk drinking limits” (US Federal Drug Administration) as optional trial endpoints. In conclusion, while abstinence remains the safest treatment goal for individuals with AD, evidence supports that reduced drinking approaches may be an important extension in the treatment of AD.